Adlay Seed (Coix lacryma-jobi L.) Extracts Exhibit a Prophylactic Effect on Diet-Induced Metabolic Dysfunction and Nonalcoholic Fatty Liver Disease in Mice. (29th May 2020) - Chiang, Hao; Lu, Hsu-Feng; Chen, Jui-Chieh; Chen, Yu-Hsin; Sun, Hsi-Tai; Huang, Hsiu-Chen; Tien, Hsiao-Hsuan; Huang, Cheng
Abstract : Nonalcoholic fatty liver disease (NAFLD) is common worldwide and closely associated with metabolic dysfunction. NAFLD leads to a higher risk of development of severe liver diseases, such as nonalcoholic steatohepatitis (NASH), liver cirrhosis, and hepatocellular carcinoma (HCC). To date, no pharmacotherapy targeting NAFLD has received general approval. Adlay is a plant that has been used as traditional herbal medicine in Asia and is a promising candidate to solve this global issue. We have established a mouse model of NAFLD by feeding a high-fat diet (HFD) for 10 weeks. Here, ethanolic or water extracts of adlay seed (ASE and ASW, respectively), mixed with HFD, were fed to the mice for 10 weeks. The ASE and ASW treatment ameliorated hyperglycemia and improved the glucose tolerance and insulin resistance in the HFD mice. Hyperlipidemia in HFD mice was prevented by the ASE and ASW diet. In addition, the ASE and ASW supplementation attenuated hepatic steatosis and inflammation, improved liver function, and caused no harm to the kidneys. Moreover, the mechanism of the effect of ASE and ASW on inhibiting hepatic lipogenesis and inducing fatty acid β -oxidation was certified by the simulated human fatty liver cell model. Our study showed the regulatory potential of the extracts of adlay seeds for alleviating NAFLD, as well as related liver and metabolic diseases.